What reading teaching practices to support learners in difficulty in the Moroccan High school ? - EL KINANI , Hamza (Revue Internationale du Chercheur, 2025)
Abstract This study addresses the question of declared reading teaching practices in the Moroccan qualifying secondary cycle, with a particular focus on supporting poor readers. The aim is to go beyond institutional observations Moroccan pupils’ reading difficulties, in order to analyze in greater analyze in greater detail the practices implemented by teachers and their their impact on struggling learners. Through quantitative quantitative research, we identify teaching practices specific to teaching the reading of literary texts, which are likely to enhance the performance of students with learning difficulties. We analyze the methods employed by a sample of twenty-four teachers, as well as the specific specific strategies they use to gradually develop their pupils’ reading skills. their pupils’ reading skills. The aim of this analysis is to improve and to adapt teaching practices to the needs of struggling the needs of struggling pupils. It takes into account the Moroccan educational context and the specific challenges associated with learning to read.